AN ANALYSIS ON THE NATURE OF TEACHER- STUDENT INTERACTION IN ENGLISH CLASS - Anugerah, Angga; Rahayu, Rahayu; Wardah, Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe research aims at analysing the teacher-student interaction in the classroombased on Foreign Language Interaction Analysis (FLINT) system in the classroom at eleventh grade students of MAN 2 Pontianak in academic year 2016/2017.This research applied a case study approach with qualitative method. The sample of this research were one English teacher as the participant who taught English subject and XI IPA 3 students.The instruments were FLINT system.The data was collected by using observationtechniquewith audio recorder as the tool of collecting data. The research findings showed that that there were two languages used in the teacher-students interaction. The languages used in the interaction were English and Indonesian which English was the dominant language used in the classroom. The teacher talk of giving praises and encouragement is approximately more than criticizing the student’ behavior , the asking questions category dominate the teacher talk category rather than student’s talk but once the teacher asked the questions to the students and the students responded it well by speaking eagerly. The utterances of giving direction occurred in relatively short times. While in student talk, there are students’ problems and difficulties in speaking. The extracts of student talk in classroom interaction revealed the students problems such as the lack of vocabulary, anxiety, inability to form ideas in English language form, and grammar error. The teacher talk frequency was still excessive, but the teacher made group and pair discussions to balance the effective talk for students in student-student interaction. Keywords: Teacher-student Interaction, FLINT System, English Class.